New Insights into the Male Morphotypes of the Amphidromous Shrimp Macrobrachium olfersii (Weigmann, 1836) (Caridea: Palaemonidae) and a Discussion on Social Dominance Hierarchies - Santos, Rafael Carvalho [UNESP]; Nogueira, Caio Santos [UNESP]; Jaconis, Milena Silva [UNESP]; Davanso, Thiago Maia [UNESP]; Costa, Rogerio Caetano [UNESP]; Hirose, Gustavo Luis (My University, 2022)
Male morphotypes in a population may lead to the development of social dominance hierarchies in crustacean species. Currently, Macrobrachium is the decapod crustacean genus with the largest record of species that present the development of hierarchies. Macrobrachium olfersii has morphological characteristics that indicate the presence of male social dominance within its populations. Thus, the present study tested the hypothesis of the occurrence of male morphotypes in M. olfersii through morphometric and morphological analysis of the chelipeds. Sampling was carried out from March 2018 to October 2021 in seven points along the Jequitinhonha River, Northeast Brazil. A total of 264 males were collected with carapace length (CL) ranging from 4.01 to 23.70 mm. Morphological sexual maturity size was estimated at 8.95 mm CL. The morphometric and morphological analysis confirmed the presence of three adult male morphotypes: M1, M2, and M3. The characterization of the different morphotypes was mainly due to the variation in size, shape, and morphology of the largest cheliped of the second pair of pereopods. Most morphometric relationships differed significantly (p < 0.01) among the three morphotypes, mainly between M3 against M1 and M2. The variation in the propodus shape was also evident. This trait and the angulation of the spines differed significantly between morphotypes (p < 0.01), with the propodus of morphotype M3 being more robust and carrying a greater number of spines than the others. The occurrence of social dominance and the exaggerated development of a cheliped (weapon) can be advantageous for dominant individuals when they need to compete for resources. This morphological trait can provide these individuals with advantages during fights and guarantee access to the best resources, whether they are shelter, food, or sexual partners. Our results add new information to the biology of M. olfersii, as well as the genus Macrobrachium, and the occurrence of social dominance in species of this group. In addition, by describing these morphotypes in detail, using a set of complementary morphological and morphometric techniques, it is possible to access the differential morphology along the M. olfersii males, as well as confirm a life history trait found in several Macrobrachium species.
Keywords: Allometry; Chelipeds; Decapoda; Geometric morphometrics; Relative growth